Penggunaan Metode Multiscale Retinex Untuk Peningkatan Bayangan dan Sorotan dengan Reflectance dan Iluminasi Citra - Bobby Syahputra Dalimunthe; Garuda Ginting (Journal of Computer System and Informatics (JoSYC), 2020)
In an image there is an image that has a highlight and shadow. The shadow that is produced from an object is highlighted by the emitted light. In this case the picture shows an object that looks faint and looks not visible at all. In overcoming this, try to increase the highlights and shadows on the image. With the process of counting and being able to count objects with reflected, transmitted, or subjective light colors. To overcome this, input values ​​of red / green / blue and balanced lighting are needed for each pixel. By using the multiscale retinex method with the help of reflectance and illumination of the image in an increase in highlights and shadows. The results that can be done in this process produce a new image that has been improved from the previous image. Applications used in Enhancing highlights and shadows use the matlab application.